Prevalence of musculoskeletal disorder among office workers in Lembaga Tabung Haji Kuala Lumpur - Harith, Noorhashirin; Zainuddin, Huda; Baharom, Anisah; Kadir @ Shahar, Hayati; Baharudin, Mohd Rafee (Community Health Society Malaysia, 2018)
Background: Musculoskeletal disorders (MSDs) are considered an important occupational health problem with consequences for workers, employers, and society. Musculoskeletal diseases (MSDs) are on the rise in Malaysia as the country moves towards industrialization coupled with the rising average age of workers. Staffs working in Lembaga Tabung Haji (LTH) are considered as office workers and play roles either in the administration or support system and high accident reported under the public administration and defence/compulsory social security compared to manufacturing. Disease of the musculoskeletal system and connective tissue were the second top cause from 45 lists of diseases for invalidity scheme under SOCSO.